Dual drive coexistence of EML4‐ALK and TPM3‐ROS1 fusion in advanced lung adenocarcinoma. Issue 2 (18th December 2017) - Zhu, You‐cai; Liao, Xing‐hui; Wang, Wen‐xian; Xu, Chun‐wei; Zhuang, Wu; Wei, Jian‐guo; Du, Kai‐qi
Abstract : We report a case of concomitant EML4‐ALK and TPM3‐ROS1 fusion in non‐small cell lung cancer (NSCLC) in a 47‐year‐old Chinese man and review the clinical characteristics of this type double of fusion. The patient presented with a local tumor of the left upper lobe and underwent thoracoscopy. Postoperative surgical pathologic staging revealed T1a N0 M0 stage IA. Histological examination of the tumor showed lung adenocarcinoma. Ventana ALK (D5F3) assay of the left lung tissue was ALK negative; however, immunohistochemical assay was positive for ROS1 protein. Using next generation sequencing, we found that the tumor had concomitant EML4‐ALK and TPM3‐ROS1 fusion. No recurrence was observed during seven months of follow‐up. Precise diagnostic techniques allow the detection of concomitant ROS1 fusion and other driver genes, including ALK or EGFR ; therefore oncologists should consider this rare double mutation in NSCLC patients. Further exploration of treatment models is required to provide additional therapeutic options.